Analisis Semiotika Struktural Saussure Dalam Kisah al-Mutharadah - Aulia Rahman; Wadi, Namlul (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study analyzes the symbols in the Arabic short story al-Mutharadah using Ferdinandd de Saussure’s structural semiotics approach. The topic is significant because literary works often contain deep symbolic meanings that require proper analytical tools for full comprehension. This study aims to help readers—especially non-Arabic speakers—grasp the social and moral messages embedded in the story by interpreting its linguistic and visual signs. A qualitative descriptive method is employed, based on an interpretive paradigm. Data were collected from both the narrative content and visual elements of the al-Mutharadah book and were analyzed using Saussure’s concepts of signifiedr and signifiedd. The study finds that visual elements, such as the whip depicted on the book cover, symbolize social criticism, highlighting the lack of moral responsibility in society. Within the narrative, the image of a breastfeeding baby represents both a mother’s love as a divine gift and the heavy burden of responsibility. The study concludes that al-Mutharadah is rich in symbolic meaning and offers strong social criticism against patriarchy and abuse of power. It recommends the use of semiotic approaches when analyzing Arabic literary texts to uncover hidden meanings in a more scientific and comprehensive manner.